2010
DOI: 10.3109/13685530903536650
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of intermittent rat parathyroid hormone (1-34) treatment on low bone mass due to oestrogen or androgen depletion in skeletally mature rats

Abstract: Rat parathyroid hormone (PTH) 1-34 (4 microg/kg/day) was applied for 2.5 months to 9 month-old rats immediately after ovariectomy or orchidectomy or to 15 month-old rats with low bone mass which had been castrated 6 months before in order to know the effects on serum biochemistry parameters, lumbar and femoral bone mineral density, histology, cancellous and cortical bone histomorphometry, mineralisation content profile in cortical bone by backscattered-electron microscopy, and femoral torsion biomechanical tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In two of these studies, 40 μg/kg/day was demonstrated to effectively accelerate fracture healing in the mouse, with enhancement of chondrogenesis and expansion of the cartilaginous callus [65, 66]. It should be noted that 40μg/kg/day is significantly higher than accepted and optimal ranges in other species including rat (4–20μg/kg/day) [69, 70], rabbit (10 μg/kg/day) [71], macaque (5 μg/kg/day) [72], and human (0.25 μg/kg/day) [73]. We anticipate that there is a similar species-associated shift in the range of effective concentrations supporting chondro-protective and chondro-regenerative effects.…”
Section: Discussionmentioning
confidence: 99%
“…In two of these studies, 40 μg/kg/day was demonstrated to effectively accelerate fracture healing in the mouse, with enhancement of chondrogenesis and expansion of the cartilaginous callus [65, 66]. It should be noted that 40μg/kg/day is significantly higher than accepted and optimal ranges in other species including rat (4–20μg/kg/day) [69, 70], rabbit (10 μg/kg/day) [71], macaque (5 μg/kg/day) [72], and human (0.25 μg/kg/day) [73]. We anticipate that there is a similar species-associated shift in the range of effective concentrations supporting chondro-protective and chondro-regenerative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Iida-Klein et al [ 32 ] showed that long bones responded to iPTH already between 1-2 weeks, whereas the increase in vertebral bone was only detected after 7 weeks in mice treated with a dose of 40 μ g/kg/day. Other studies also reported that the hormone has skeletal site-specific action, promoting the cortical increase through a mechanism that involves increased in both bone formation and resorption in the cortical bone [ 33 36 ].…”
Section: Discussionmentioning
confidence: 99%